2006
DOI: 10.1063/1.2213181
|View full text |Cite
|
Sign up to set email alerts
|

Flame synthesis of aligned tungsten oxide nanowires

Abstract: Aligned single-crystal WO2.9 nanowires are grown directly from tungsten substrates at high rates using a flame synthesis method. The nanowires have diameters of 20–50nm, lengths >10μm, coverage density of 109–1010cm−2, and growth rates >1μm∕min. Growth occurs by the vapor-solid mechanism, with local gas-phase temperature (∼1720K) and chemical species (O2, H2O, and H2) strategically specified at the substrate for self-synthesis. Advantages of this synthesis method are reduced processing times, abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 20 publications
2
50
2
Order By: Relevance
“…The precursor materials decompose and the produced metals oxidize in a well-controlled flame yielding a uniform nanosized oxide powder product. More recently, the formation of narrow-sized and specifically shaped nano-oxide particles or nanofibers was achieved by flame synthesis performed over specifically prepared substrates introduced in well-controlled flat flames [82]. Alternately, external electric fields can be used to control the formation of oxide nanoparticles and their agglomeration [83].…”
Section: Additional Nanopowdersmentioning
confidence: 99%
“…The precursor materials decompose and the produced metals oxidize in a well-controlled flame yielding a uniform nanosized oxide powder product. More recently, the formation of narrow-sized and specifically shaped nano-oxide particles or nanofibers was achieved by flame synthesis performed over specifically prepared substrates introduced in well-controlled flat flames [82]. Alternately, external electric fields can be used to control the formation of oxide nanoparticles and their agglomeration [83].…”
Section: Additional Nanopowdersmentioning
confidence: 99%
“…[20][21][22][23] Tungsten oxide has variant suboxide crystal structures. [24][25][26][27][28] Among these, one of the well-known structures is a monoclinic W 18 O 49 , which is highly anisotropic and shows a good mechanical strength. 29 Various methods based on thermal treatments, vapor phase growth, oxidation, and wet chemical reaction have been reported for preparing W 18 O 49 nanowires.…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to note that of all the tested transition metals in this study, only the W-oxide structures were coated with a thick layer of highly crystalline carbon. Xu et al [35] reported that the flame synthesis of nanorods composed of W, O and traces (c) (1) of C. Their results suggest that the presence of C is most likely from the deposition of C on the nanowires from carbon-containing species that diffuse from the reaction zone during the processing [35]. The application of HRTEM analysis to our products revealed that a very uniform thick layer of graphite covers the tungsten oxide nanowires.…”
Section: Synthesis Of 1d W-oxide Nanowiresmentioning
confidence: 79%